Short‐term effects of a novel bronchial drainage device: A pilot cohort study in subjects with cystic fibrosis. Issue 5 (12th September 2022) - Schmidt, Hanna; Toth, Monika; Kappler‐Schorn, Christine; Siebeneich, Ute; Bode, Sebastian F. N.; Fabricius, Dorit
Abstract: Background and Aims: In cystic fibrosis (CF) airways, impaired airway mucociliary clearance and mucus accumulation due to cystic fibrosis transmembrane conductance regulator defects contribute to inflammation, progressive structural lung damage, and decline of lung function. Physiotherapy is essential to promote mucus mobilization and removal in CF and is a key element of rehabilitation measures, but conventional techniques may be suboptimal to mobilize viscous mucus. This study aimed to test the specific effects of a novel bronchial drainage device (BDD) (Simeox®; PhysioAssist) in subjects with CF and evaluate lung function, diaphragm mobility, and sputum properties. Methods: This prospective monocentric clinical cohort study in the setting of outpatient physiotherapy of CF patients ( n  = 21) with stable CF lung disease collected pulmonary lung function tests (PFT), diaphragm mobility, and sputum properties before and after two physiotherapy sessions using the novel BDD. PFT was assessed using spirometry and diaphragm mobility using m‐mode ultrasound analysis. Spontaneous sputum samples were collected before and after using the BDD and analyzed for microstructure and DNA concentrations. Results: PFT parameters (FEV1, FVC, MEF25/50/75) were not affected by the use of the BDD. Ultrasound analysis of diaphragm mobility revealed an increase in maximum diaphragm excursion upon the intervention. Mucus analysis demonstrated altered microstructure and higher DNA concentrations collected after using the BDD compared to samples collected before. Pearson correlation analysis showed significant correlations between changes in mucus properties and DNA levels in respective mucus samples. Conclusion: Our results demonstrate that the novel BDD improves diaphragm mobility and alters sputum properties in subjects with CF. The novel BDD with unique properties may be further studied as a device in CF‐specific physiotherapy to facilitate sputum mobilization of CF patients.